Cytochrome P450 Epoxygenase Dependence of Opioid Analgesia: Fluconazole Does Not Interfere With Remifentanil‐Mediated Analgesia in Human Subjects. Issue 6 (22nd August 2014) - Oertel, B G; Vermehren, J; Huynh, T T; Doehring, A; Ferreiros, N; Zimmermann, M; Geisslinger, G; Lötsch, J
<x xml:space="preserve">Abstract</x> Cytochrome P450 (CYP) inhibitors may reduce opioid analgesia by inhibiting CYP activity–dependent post–opioid receptor signaling pathways in the brain. This suggestion was predicated on observations of highly attenuated morphine antinociception in rodents after intracerebroventricular injection of fluconazole or carrying a neuron‐specific deletion of the cytochrome P450 reductase. However, based on assessments of thermal and electrical pain tolerance, respiratory function, and side effects in 21 healthy volunteers, before and during steady‐state concentrations of 1.5 and 3.0 ng/ml of remifentanil at the effect site (viz., the central nervous system), administration of 400 mg/day fluconazole for 8 days in a double‐blind, placebo‐controlled manner failed to attenuate opioid effects. Although CYP inhibitors such as fluconazole are unlikely to attenuate remifentanil analgesia in humans, extrapolation of the findings to other opioids is premature because differences among opioid effects, such as ligand‐selective biased signaling at opioid receptors, leave the possibility that CYP‐dependent opioid signaling in the brain might be limited to morphine and may not extend to remifentanil. Clinical Pharmacology & Therapeutics (2014); 96 6, 684–693. doi:10.1038/clpt.2014.169